Structure of SnO2 alcosols and films prepared by sol-gel dip coating - Rizzato, A. P.; Broussous, L.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Elsevier B.V., 2001)
To obtain SnO2 films to be used for surface protection of fluoride glasses, a non-aqueous sol-gel route for the preparation was developed. An ethanolic SnO2 colloidal suspension was prepared by thermohydrolysis of SnCl4 solution at 70 degreesC. By using this procedure, redispersable powders with nanometer sized particles were obtained. Films were obtained by dip coating on glass and mica substrates. The structures of the ethanolic precursor suspension and films were compared to those of similar samples prepared by the classical aqueous sol-gel route. Comparative analyses performed by photon correlation spectroscopy demonstrated that the powders obtained by freeze-drying are fully redispersable either in aqueous or in alcoholic solutions at pH greater than or equal to 8. As prepared sols and redispersed colloidal suspensions have hydrodynamic radius distribution (2-14 nm) with an average size close to 7 nm. The variations in film structures with firing temperature were investigated by small-angle X-ray scattering and X-ray reflectometry. The experimental results show that the films have a two level porous structure composed of agglomerates of primary colloidal particles. The sintering of the primary particles leads to the densification of agglomerates and to the formation of inter-agglomerate spatially correlated pores. The volume fraction of intra-agglomerate pores is reduced from approximate to 50% to approximate to 30% by the precipitation of precursor salts partially hydrolyzed in ethanolic solution. (C) 2001 Elsevier B.V. B.V. All rights reserved.